Continuity of care: evaluating a multidisciplinary care model for people with early CKD via a nationwide population-based longitudinal study - Yin-Cheng Chen; Shuen-Fu Weng; Yu-Juei Hsu; Chung-Jen Wei; Chiung-hsuan Chiu (BMJ Open)
Objectives To control and prevent the burdens associated with chronic kidney disease (CKD), Taiwan’s National Health Insurance Administration (NHIA) launched the ‘early-CKD programme’ in 2011 to extend care and education to patients with CKD. This study aims to evaluate the effectiveness of the early-CKD programme in terms of continuity of care (COC).Design and participants This study used secondary data from 2010 to 2014 provided by the NHIA to identify 86 581 participants each for the intervention and control groups. Patients with CKD who participated in the early-CKD programme between 2011 and 2013 were defined as the intervention group. For the control group, propensity score matching was used to select patients with CKD who did not participate in the programme, but were seen by the same group of physicians.Intervention A multidisciplinary care model for patients with early CKD launched in 2011.Primary outcome measures Outcome variables included the continuity of care index (COCI), which measures a physician’s COC; number of essential examinations; and resource utilisation. To better identify the difference between groups, we separated COCI into two groups based on mean: high (above mean) and low (below mean). A generalised estimating equation model was used to examine the effects of the early-CKD programme.Results The programme significantly increased the number of essential examinations/tests administered to patients (β=0.61, p<0.001) and improved COCI between physicians and patients (OR=4.18, p<0.001). Medical expenses (β=1.03, p<0.001) and medication expenses (β=0.23, p<0.001) significantly increased after the programme was implemented, but patients’ kidney-related hospitalisations and emergency department visits decreased (β=−0.13, p<0.001).Conclusion From the COC viewpoint, the programme in Taiwan showed a positive effect on COCI, number of essential examinations and resource utilisation.